The voyage of the Dawn Treader - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia (HarperCollins (Firm)), 1994)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.